Nitrous Oxide Utility in Labor and Birth: A Multipurpose Modality. Issue 2 (April 2017) - Collins, Michelle
Abstract : The use of nitrous oxide (N2 O) for labor and birth has very recently emerged as a viable modality in the United States, despite a long history of use in Canada and Europe. Usually associated with dental procedures, there are significant differences between dental and parturition utility, efficacy, and staff exposure. In addition to using it for pain relief and anxiolysis, those centers utilizing it have noted it to be multipurpose and useful for such situations as: external cephalic version, manual removal of placenta, intravenous starts, during placement of urinary catheters and intracervical Foley bulbs. Nitrous oxide has proven to be especially helpful for repair of lacerations under local anesthesia and is a multiuse modality that should be available to women in all birth settings. This article explores the history of N2 O use, provides a comparison of obstetrical use to use in the dental industry, examines the contraindications to, and implications for usage, and discusses logistical points of consideration for clinicians working with women using N2 O for labor and birth.